2022
DOI: 10.1007/s11332-022-01031-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between objectively measured sitting time, posture, and low back pain in sedentary employees during COVID-19

Abstract: Purpose The purpose of this study was to examine the relationship between objectively measured sitting time, posture, and low back pain (LBP) in adults with full-time (≥ 40 h/week) sedentary “desk” jobs. Physical activity (PA) and sedentary behavior (SB) between work environments (home vs. office) were also compared during COVID-19. Methods Participants ( N = 53; M age = 41 ± 12years) were full-time em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Most of the backpacks weighed less than 4 kg, with 49.5% being 1-2 kg and 40.8% being 3-4 kg. Table (7) presents the relationship between carrying a backpack and developing LBP. Out of 319 participants who carried bags, 221 reported feeling back pain at some point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the backpacks weighed less than 4 kg, with 49.5% being 1-2 kg and 40.8% being 3-4 kg. Table (7) presents the relationship between carrying a backpack and developing LBP. Out of 319 participants who carried bags, 221 reported feeling back pain at some point.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that LBP is quite common among healthcare workers (5) , and in some cases, it even predates their career commencement (6) . This challenges the conventional wisdom that LBP predominately affects older individuals, as it is frequently also found among adolescents (7) . According to the available literature, medical students in advanced semesters undertaking increased hospital-based practical activities experience a higher prevalence of LBP compared to their juniors (4) .…”
Section: Introductionmentioning
confidence: 87%
“…seamstresses falling within the range of 1 to 5 years. 14 Tailors engaged in prolonged static sitting positions often face risks related to poor work posture, which can ultimately contribute to the onset of lower back pain. Tailors often sit in front of sewing machines or work tables for extended periods.…”
Section: Original Articlementioning
confidence: 99%

The correlation between work posture and lower back pain among tailors

Putu Ayu Bintang Anjali,
Sayu Aryantari Putri Thanaya,
Agung Wiwiek Indrayani
et al. 2024
ptji
“…It has been shown that Low back pain (LBP) is one of the most common musculoskeletal disorders ( Ghanei et al, 2013 ). Nowadays, non-ergonomic working conditions increase the amount of time people spend sedentary, incorrect Sedentary Posture May Exacerbate People's Low Back Pain ( Butte et al, 2022 ). Young adult college students who spend too much time sitting in a slouched position while studying, using a computer, or during daily activities are more likely to have spinal disorders and pain ( Toprak ÇElenay and ÖZer Kaya, 2017 ).…”
Section: Introductionmentioning
confidence: 99%